كاریگه‌ری پڕۆگرامێكی فێركاری-فێربوون له‌سه‌ربنه‌مای فێربوونی چالاك له‌گه‌شه‌پێدانی بیركردنه‌وه‌ی داهێنه‌رانه‌ لای قوتابیانی پۆلی هه‌شته‌می بنه‌ڕه‌تی (توێژینەوەی هەڵێنجراو) - محمد, سۆلاڤ فائق; أمین, عبدالله‌ كریم; ڕوستم, مریم محمد (Sulaimani Journal for Humanities, 2023)
The main purpose of this research is to know "the effect of a learning-learning program on the principle of active learning in developing inventor's thinking to eighth grade students" Using the type of experience method, the research needs that he finds himself in two programs between a teacher's and teacher's work program, the second of which is a special training program Students, in three stages such as planning, implementing, evaluating, as well as taking and using the test of thinking about the invention of Turans, which has been created in three different activists Such as "images, non-complete images, circles" each of these activists includes four skills such as (speed, sheer representation, originality, clarification), which develop the Students more educated to get the information, and then honesty is given to the measure based on the opinions of the majority of experts. The stability has been found in the form of a re-examination that has been done on 200 students outside the research sample, and directing the result By using Person's co-ordination after conceding the results of the stable value of 91%, it has been adapted for research. The researcher determined of the research group that the number of them in general (18699) was based on two education directorates of east and west, in the center of Sulaymaniyah governorate, the example The research taken from it in a simple form of Qura in shadi basic school is based on western education directorate, which is assigned to two groups There is a difference between the experience group, which has a total number of 30 male and female students, a centralized group, and a number of 29 male students. Similarities have been found for the groups to receive each of the graves (age, examinations of 6-7, parental profession, parental certificate, intelligence, grade 7 test), and after being sure of the truth and stability of the order Co-coordinating the groups, the research was carried out to both experience groups and the Centralized group, which is an experience group through both educational-learning programs, and the International Group through Normally, they studied for the academic year (2022-2023), after the completion of the research experience, inventive testing for both groups, to find out the purpose of the research according to nature. The research used by the statistical coordinator "such as Person's coordinator, Kai Square, census center, T.test deviation, in the name of (SPSS) In the midst of testing both research groups, knowing the application of a learning-learning program is in the interest of the experience group in using the programs. The recommendations of the research are using a learning-learning program in the course of active learning in developing inventor's thinking to the students of the eighth grade Using a program prepared in the curriculum for geography teachers, and opening training courses for teachers, they learned how to learn actively. Definition of the term "research" is an educational-learning program, active learning, and inventor's thinking.